Performance and Acceptability of a Combined Device for Insulin Infusion and Glucose Sensing in the Home Setting. (14th January 2015) - Nørgaard, Kirsten; Shin, John; Welsh, John B.; Gjessing, Hans
Background: The use of sensor-augmented insulin pump (SAP) therapy is increasing. Currently, glucose sensors and insulin infusion cannulas are inserted separately. A new device, MiniMed Duo, combines sensing and infusion capabilities on the same platform and is intended to simplify device insertion and site management. We evaluated the device's performance with respect to insulin delivery and glucose sensing, and its acceptability with patients. Methods: Forty-five patients (mean ± SD age, 45.5 ± 10.9 years, 48% female) with type 1 diabetes and previous use of SAP participated. Each subject was to wear 5 devices connected to insulin pumps over 15 days (3 days/device) and test capillary blood glucose (SMBG) 7 times/day. The primary endpoint was the percentage of sensor-SMBG paired values within 20% of one another. Subject experiences were assessed via questionnaires. Results: Overall, 74.8% of sensor-SMBG paired values were within 20%, meeting the primary accuracy endpoint, and the mean absolute relative difference was 15.5 ± 17.1%. Consensus error grid analysis showed that >95% of points were within the A+B zones, exceeding the threshold for adequate clinical accuracy. Insulin dosage and SMBG values did not change significantly compared to prestudy values. The functional survival of the device entering day 3 was 90.5%. There were no serious adverse events. Mean questionnaire results indicated overall satisfaction with the device. Conclusion: Duo provided insulin infusion and glucose sensing capabilities in a single device, which provided accurate glucose readings during routine use, was safe to wear, and was acceptable to most patients. It may improve satisfaction and convenience for patients using sensor-augmented insulin pumps.